BUTIN-2-DIOL-1,4 OLINISHI VA UNING XOSSALARI - Turg‘unov , Erxan; Nizamov , Isomiddin; Sodiqov , Mansur (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
This thesis presents data on the study of the catalytic synthesis of butin-2-diol-1,4 and the production of its esters.